STUDY OF THE CORRELATION BETWEEN THE ABO BLOOD TYPE SYSTEM AND HYPERTENSION IN ADOLESCENT IN PADANG HARAPAN, BENGKULU - Putra Adi Irawan; Tedy Febriyanto (GEMA KESEHATAN, 2022)
Hypertension cases increase every year, around 1.13 billion people in the world suffer from hypertension. Hypertension in Indonesia is a risk factor for death, stroke, and ischemic heart disease. Around 23.8% of the Indonesian population aged 18 years and over have hypertension. The prevalence of hypertension in the population aged 18 years is 34.1% per 300,000. Patients with hypertension with an age range of 18-34 years amounted to 33.3%. Data on the population of Bengkulu Province with age above 18 years in the year 2016, with reported hypertension conditions, amounted to 12,675 (54.66%) per 730,285. In 2018, cases of hypertension in Bengkulu City were 2,186. Data on the ABO system blood group based on a history of hypertension in Padang Harapan is still lacking. This research is an analytical observation using a cross-sectional approach. Respondents were teenagers aged 17-25 years, 508 people were selected by purposive sampling. The study took place from March-December 2021. Hypertension in 508 adolescents in Padang Harapan was relatively small, namely 26 (6.7%). Hypertension cases in non-O blood groups (A, B, AB) were more than 19 cases, compared to only 7 cases for blood type O. Adolescents with blood type B were more likely to have hypertension (9 cases). The relationship between hypertension and blood type in adolescents in that location is very weak (α> 0.05). The blood type of the ABO system in adolescents in Padang Harapan is dominated by blood type A (33.7%), followed by blood type O (32.7%), B (23.2%), and AB (10.4%). 6.7% (N=508) of teenagers had hypertension, which was dominated by blood type B, followed by blood types A, O, and AB. There was no significant (Ho) relationship (p>0.05) between the ABO blood group system and hypertension in adolescents. Keywords: ABO blood type, Adolescent, Hypertension